Ações do Núcleo de Acessibilidade na EAD de uma Instituição de Educação Superior Privada e a satisfação dos estudantes com deficiência - Fantacini, Renata Andrea Fernandes (2017)
There is a growing debate about the inclusion of students with disabilities in Higher Education, since the official documents of the Ministry of Education guide Higher Education Institutions to the creation of Accessibility Programs. Once the Accessibility Nucleus was set up in a Private Higher Education Institution, the interest arose to check how it happened the articulation of the principles of inclusion and formulation of the institutional practices policies in the pedagogical scope and of the management in the undergraduate distance courses in that institution. The general objective of this research was to describe and analyze how the actions of this Accessibility Nucleus were taking place in undergraduate courses of the Distance Education modality of a Private Higher Education Institution and to evaluate the satisfaction of students with disabilities in relation to these actions. This research was carried out in the Nucleus of Accessibility of a private Institution. This is a documental, exploratory and descriptive research, with a quantitative and qualitative approach. Participated in this research, five teachers who make up the Accessibility Nucleus and 21 students who declared themselves to be students with disabilities participated in this research and requested support from the Accessibility Nucleus. The results show that the members of this Accessibility Center are adequately trained to perform this function; that through the mapping the students with disabilities, it was possible to verify that the Institution had, by the end of 2016, 137 students with disabilities included in its Distance Education courses. However, only 26 students with disability confirmed their self-declaration and requested some kind of help from the Accessibility Nucleus. Finally, it was possible to know through the application of the Satisfaction and Attitudes - ESA Scale the level of satisfaction and attitudes of this population in relation to the actions of the Accessibility Nucleus, in addition to making it possible to identify and point out some ways to overcome structural, operational, psycho-affective barriers and attitudes towards obstacles. It was concluded that the measurement of the level of satisfaction of this population is necessary and can contribute to the construction of inclusive contexts in Distance Education of this institution and, this study, can constitute an important tool for the Accessibility Nucleus, in the sense of to help develop actions not only to follow and monitor the actions implemented, but also to ensure the inclusion in Higher Distance Education of this Higher Education Institution, can bring contributions for other institutions. It is suggested that: other research on this topic be developed, as well as the implementation of Specialized Educational Assistance in Higher Education; the formation of a collaborative consulting team; the creation of permanent training programs for the entire academic community, aiming at promoting the inclusion of students with disabilities in the university environment, as well as the implementation of specific programs in university settings.